Case Report: Transient hypertension and myalgia following mavacamten therapy in a patient with hypertrophic obstructive cardiomyopathy - Peng, Mengling; Fu, Yu; Qin, Cong; Zhou, Shanshan; Sun, Jian (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMavacamten has been demonstrated to be effective in the treatment of hypertrophic obstructive cardiomyopathy (HOCM). However, its hemodynamic impact and extracardiac effects require further characterization.Case presentationWe report a case of a 68-year-old female diagnosed with severe HOCM who experienced transient hypertension (165/105 mmHg) and myalgia four weeks after mavacamten initiation. Despite a significant reduction in LVOT obstruction (from 64 mmHg–18 mmHg) and an increase in LVEF to 78%, the patient exhibited a transient hypertensive response that resolved spontaneously within two weeks without intervention. Myalgia was present without corresponding elevations in serum creatine kinase.ConclusionsThis case highlights a previously unrecognized transient hypertensive phase associated with myosin inhibition, potentially related to ventriculo-arterial decoupling and peripheral vascular adaptation. Additionally, the dissociation between myalgia and CK elevation suggests alternative skeletal muscle involvement mechanisms. Close blood pressure monitoring and further investigation into the extracardiac effects of mavacamten are warranted.